PENGARUH INITUITIVE ACCURACY, TRUST, PARTICIPATION, DAN EFFORT TERHADAP SALES PERSON PERFORMANCE PRODUK PT. KIARA DI KOTA YOGYAKARTA - Wasiman Wasiman (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine the effect of inituitive accuracy, trust, participation, and effort partially to salesperson performance and also simultaneously to sales person performance PT KIARA. This research is aquantitative descriptive research by using questionnaires. The population in this research is all consumersPT. KIARA in Yogyakarta who shop at the Nisrina Clinic, Qeza Clinic, Fortune Clinic, MJ Scin care clinics,and AHA skin care clinic which obtained 89 samples by purposive sampling method. The analysis techniqueused is a multiple linear regression equation with a significance level of 5%. The results showed thatinituitive accuracy had positive significant effect on the sales person performance, trust had positivesignificant effect on the sales person performance, participation had positive significant effect on the salesperson performance, effort had positive significant effect on the sales person performance andsimultaneously inituitive accuracy, trust, participation influence had positive significant effect to salesperson performance PT. KIARA.